Why the case for a multilateral agreement on investment is weak - Peter Nunnenkamp; Manoj Pant (Institut für Weltwirtschaft (IfW), 2003)
The demand of industrialized countries for a multilateral agreement on investment to be negotiated under the roof of the WTO is meeting with considerable resistance on the part of developing countries. The proponents of such a multilateral agreement argue that binding disciplines of capital-importing countries would help reduce uncertainty and, hence, result in more foreign direct investment (FDI) in developing countries. By contrast, the opponents consider such an agreement to be biased in favor of business interests and against the development objectives of Third World economies. It is for various reasons that the case for a multilateral agreement on investment is not compelling: Investment regulations have been liberalized progressively by unilateral measures without multilateral obligations to do so. Moreover, the protection of foreign investors against political risk is fairly advanced given the large number of bilateral and plurilateral investment treaties. A multilateral agreement could reduce FDI-related transaction costs significantly only in the unlikely event that the complex net of existing arrangements would be replaced. A “WTO plus”-type framework appears to be the more realistic outcome of negotiations, with a multilateral agreement defining the smallest common denominator of WTO members and more substantive agreements with limited membership remaining in place. Empirical evidence suggests that WTO negotiations on investment are neither sufficient nor necessary to induce higher FDI flows to developing countries. Transaction-cost-related impediments to FDI have played a minor role in driving FDI, and the absence of a multilateral agreement has not prevented the recent boom of FDI in developing countries. Wishful thinking prevails on the part of developing countries, which insist on preferential treatment with regard to their own obligations as host countries and on binding obligations for foreign investors and their home countries. It is highly questionable whether developing countries could derive more benefits from FDI if a multilateral agreement were to include “development clauses” allowing for flexible and selective approval procedures and performance requirements such as local-content rules. The call for binding rules on the behavior of foreign investors may discourage multinational enterprises from investing in developing countries altogether, instead of fostering transfers of technology and improving the quality of FDI. By insisting on preferential treatment with regard to FDI incentives, developing countries tend to ignore that incentives- based competition for FDI is mainly between themselves. Unless developing countries are prepared to tie their own hands, they cannot reasonably expect significant concessions from industrialized countries. Developing countries will become relevant negotiation partners in the WTO only by offering something on their own. Rather than engaging in a futile attempt to block multilateral negotiations on investment altogether, developing countries should commit themselves to rulebased FDI policies as a negotiating chip. The pressure on industrialized countries to engage in negotiations on labor mobility would mount if developing countries refrained from performance requirements and granted national treatment to foreign investors.
Keywords: 330; Direktinvestition; Investitionsgarantie; Handelsabkommen; WTO-Regeln; Welt